Sistem Layanan Sirkulasi di Perpustakaan Proklamator Bung Hatta Bukittinggi - Cintia, Tega D.; Yunaldi, Yunaldi (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
This article is aimed to (1) describe the system of circulation service at Proklamator Bung Hatta Bukittinggi Library (PPBH); (2) describe the activity of administrating on circulation service at PPBH. From the result of my research, I can conclude (1) the circulation service at PPBH looks does not work optimally yet because of the numerous queues on circulation desk. It caused by the place of collection renting and returning gathered in one place. Besides, the circulation service also looks does not work optimally because of the lack of staff, where the staff who serves the circulation is only one person; (2) the activity of collections renting at PPBH uses card/ renting slip, where when a visitor wants to rent a collection, the staff will write the date of renting, the date of returning, and the classification number of the book, and then it will be signed by the visitor. The activity of returning at PPBH is when the collections is being returned, the staff will check the id card of library member and the date of returning on the book’s bag, if there is a lateness of returning, the staff will ask for the fee of lateness to the visitor and write it on a sheet of fee of lateness; (3) maximize the work of the staff. Based on the result of my research, then I suggest to PPBH to separate the place of renting and returning the collections, and add some more staff of circulation division. Keywords: system of circulation services; library administrations